Pengaruh pendidikan kesehatan tentang kanker serviks terhadap minat pemeriksaan IVA pada kelompok ibu pengajian - Sugiyanto Sugiyanto; Tya Nur Febriana (Jurnal Kebidanan dan Keperawatan Aisyiyah, 2016)
Abstract: The research was aimed to determine the effect of healtheducation about cervical cancer to the interest in VIA examination ofmother group recitation in Dusun Kramatan Gamping SlemanYogayakarta. The method used in this research was pra-eksperimenwith one group pretest-posttest design. Respondents were 25 motherstaken by purposive sampling. Paired t-test result show that p value =0,000 (0,0000,05) which means that there were a significant differencesin interest in VIA examination before and after health education.